Engineering Faculty Indicate High Levels of Awareness and Use of the Library but Tend to Consult Google and Google Scholar First for Research Resources - Sullo, Elaine (Evidence Based Library and Information Practice, 2016)
A Review of: Zhang, L. (2015). Use of library services by engineering faculty at Mississippi State University, a large land grant institution. Science & Technology Libraries, 34(3), 272-286. http://dx.doi.org/10.1080/0194262X.2015.1090941 Objective – To investigate the engineering faculty’s information-seeking behaviour, experiences, awareness, and use of the university library. Design – Web-based survey questionnaire. Setting – The main campus of a state university in the United States of America. Subjects – 119 faculty members within 8 engineering departments. Methods – An email invitation to participate in a 16-item electronic survey questionnaire, with questions related to library use, was sent in the spring of 2015 to 119 engineering faculty members. Faculty were given 24 days to complete the survey, and a reminder email was sent 10 days after the original survey invitation. Main Results – Thirty-eight faculty members responded to the survey, representing a response rate of 32%. Overall, faculty had a high level of use and awareness of both online and physical library resources and services, although their awareness of certain scholarly communication services, such as data archiving and copyright advisory, was significantly lower. Faculty tend to turn to Google and Google Scholar when searching for information rather than turning to library databases. Faculty do not use social media to keep up with library news and updates. The library website, as well as liaison librarians, were cited as the primary sources for this type of information. Conclusions – The researcher concludes that librarians need to do a better job of marketing library resources, such as discipline-specific databases, as well as other library search tools. Because faculty use web search engines as a significant source of information, the author proposes further research on this behaviour, and suggests more action to educate faculty on different search tools, their limitations, and effective use. As faculty indicated a general lack of interest in integrating information literacy into their classes, the researcher notes that librarians need to find ways to persuade faculty that this type of integrated instruction is beneficial for students’ learning and research needs. Faculty were aware of the library liaison program, so this baseline relationship between faculty and librarian can serve as an opportunity to build upon current liaison services and responsibilities.